MANAJEMEN PEMASARAN SAWI (Brassica Juncea) DI HIDROPONIK CENTER PALEMBANG - lestari, Sri Rahayu Endang (Jurnal AGRIBIS, 2021)
Based on the research, it can be concluded that, hydroponic vegetable marketing management goes through the stages of planning, implementing, and monitoring the combination of the marketing mix. The product marketing planning stage consists of selecting the type and quantity of products, market surveys, designing marketing strategies and programs. Then implemented into the production process and do marketing. Distribution planning is to determine specific consumers who believe in and accept organic vegetable products. The distribution channel is a short channel, namely from farmers to consumers. Promotion is carried out by socializing through agricultural development fairs and trying internet information technology. The advantages of hydroponic cultivation are:the crop production higher, more controlled pests in plants, faster growth of plants, more efficient use of fertilizers and easier maintenance.